Current Knowledge Regarding the Interaction Between Oral Bone Metabolic Disorders and Diabetes Mellitus - Wang, Xiaofeng; Wang, Huiyu; Zhang, Tianfu; Cai, Lu; Kong, Chenfei; He, Jinting (Frontiers in Endocrinology, 2020)
Diabetes mellitus, a major chronic disease affecting human health, has been increasing in prevalence in recent years. Diabetes mellitus can cause bone metabolic disorders in patients, leading to osteoporosis, a higher risk of traumatic fracture, and other bone diseases. Bone metabolic disorders in the oral cavity principally manifest as periodontitis, loss of alveolar bone, and failure of implant osseointegration. In recent years, numerous studies have shown that there is a complex interaction between bone metabolic disorders and diabetes mellitus. This paper reviews the adverse effects of diabetes on oral bone metabolism disorders such as alveolar osteoporosis and bone loss in patients with periodontitis, discusses the potential mechanisms of diabetic bone loss, and suggests potential ways to prevent and treat oral bone loss in patients with diabetes mellitus.